Expanding north: first record of the beaded sea cucumber Euapta lappa at Madeira Island - Schäfer, Susanne (Journal of the Marine Biological Association of the United Kingdom, 2023)
Abstract This study provides the first record of the beaded sea cucumber Euapta lappa at Madeira Island. A single individual was observed during a nocturnal scuba dive at 17 m depth, presumably feeding. After having its previous northern limit in the North-east Atlantic at the Selvagens Islands, this record expands the known distribution and northern limit of this tropical species by about 300 km. This new record of yet another tropical species expanding its range northwards can be seen as another indication of the ongoing tropicalization in the marine environment of Macaronesia in the North-east Atlantic.